Survey evaluations of University of British Columbia residents’ education and attitudes regarding palliative care and physician assisted death - Spicer, David; Paul, Sonia; Tang, Tom; Chen, Charlie; Chase, Jocelyn (Canadian Medical Education Journal, 2017)
Background: Little prior research has been conducted regarding resident physicians’ opinions on the subject of Physician Assisted Death (PAD), despite past surveys ascertaining the attitudes of practicing physicians towards PAD in Canada. We solicited British Columbia residents’ opinions on the amount of education they receive about palliative care and physician assisted death, and their attitudes towards the implementation of PAD. Methods: We conducted a cross sectional, anonymous online survey with the resident physicians of British Columbia, Canada. Questions included: close-ended questions, graded Likert scale questions, and comments. Results: Among the respondents (n=299, response rate 24%), 44% received ≥5 hours of education in palliative care, 40% received between zero and four hours of education, and 16% reported zero hours. Of all respondents, 75% had received no education about PAD and the majority agreed that there should be more education about palliative care (74%) and PAD (85%). Only 35% of residents felt their program provided them with enough education to make an informed decision about PAD, yet 59% would provide a consenting patient with PAD. Half of the respondents believed PAD would ultimately be provided by palliative care physicians. Interpretation: Residents desire further education about palliative care and PAD. Training programs should consider conducting a thorough needs assessment and implementing structured education to meet this need.